Elevated Serum Reactive Oxygen Species Level Predicts Early Abortion - Joserizal Serudji; Nuzulia Irawati; Johanes Cornelius Mose; Hirowati Ali; Yusrawati Yusrawati (Molecular and Cellular Biomedical Sciences, 2021)
Background: Impaired trophoblast invasion is associated with early abortion. The calorie needed for the trophoblast cell (TC) invasion is mainly met by adenosine triphosphate (ATP) produced in the mitochondria. Reactive oxygen species (ROS), byproduct of ATP synthesis, plays an important role in cellular physiology, but a high level of ROS may result in deoxyribonucleic acid (DNA) damage or cell dysfunction, thereby impaired TC invasion leading to early abortion. The study aims to determine elevated serum ROS level to predicts early abortion.Materials and method: This was an observational study with a cross-sectional design. Fifty subjects with gestational age less than 12 weeks, consist of 25 early abortions and 25 normal pregnancies subjects, were included in this study. Clinical examination and diagnosis are carried out in 2 Hospitals and 5 Public Health Centers in Padang. Examination of ROS levels was carried out by enzyme-linked immunosorbent assay (ELISA) in the Biomedical Laboratory, Faculty of Medicine, Universitas Andalas. The Mann-Whitney test was used to analyze the difference of serum ROS levels, with a significance level of 0.05.Results: The subjects of the two study groups were equivalent in terms of age, gestational age, and gravidity (p=0.051, p=0.453, and p=1.000). The median ROS levels were found to be 1.36 (1.02-26.30) ng/mL in the early abortion and 1.20 (0.43-2.75) ng/mL in the normal pregnancy (p=0.003).Conclusion: There is a significant difference between ROS levels in early abortion and normal pregnancy.Keywords: ROS, early abortion, normal pregnancy